Back Cover: Self‐Assembly of a Giant Tetrahedral 3 d–4 f Single‐Molecule Magnet within a Polyoxometalate System (Angew. Chem. Int. Ed. 51/2015). Issue 51 (4th November 2015) - Ibrahim, Masooma; Mereacre, Valeriu; Leblanc, Nicolas; Wernsdorfer, Wolfgang; Anson, Christopher E.; Powell, Annie K.
Abstract : A giant 3d/4f/POM tetrahedron was prepared through a one‐pot self‐assembly process which combines 4f and 3d/4f coordination cluster chemistry with polyoxometalate (POM) chemistry. In their Communication on page 15574 ff., M. Ibrahim, A. K. Powell et al. describe how trilacunary [GeW9 O34 ] 10− POMs are used as superligands to construct the nanoscale hybrid anion [(GeW9 O34 )2 Dy III 3 (µ‐OH)3 (H2 O)6 Co II 2 Dy III 3 (µ3 ‐OH)6 (OH2 )6 4 ] 56−, which contains 30 Dy III, 8 Co II, and 108 W VI metal centers, and exhibits single‐molecule magnet behavior. It contains the largest number of 4f ions of any POM system reported to date.